Attractiveness of The Slovak Market in Terms of Development of The Working Environment for Foreign Investors - Zuzana ROSNEROVA; Ladislav VAGNER (Communications of International Proceedings, 2020)
In today's business environment, the global economy creates more opportunities for everyone, but also more risks, as it is scaled by a wide dimension of information and communication technologies, international integration or the maturity of domestic markets. There are several possibilities for increasing the attractiveness of each country for foreign investors, while many of them also have favourable effects on the economy as a whole. The paper focuses on the evaluation of the macroeconomic development of regional disparities of individual regions of the Slovak Republic through the forecast of economic development in individual blocks of the macroeconomic module of Slovakia's regionalization. The aim of the article is to assess the attractiveness of the market of the Slovak Republic for foreign investors in terms of regional disparities and to assess the possibilities of eliminating the identified disparities through the use of foreign capital. The hypothesis we are working on in the article proved to be true, because it was confirmed on the basis of the analytical part of the article.
Keywords: Region; Regional Disparities; Labour Force; Economically Active Population; Foreign Investment.